Estimating freshness of ice storage rainbow trout using bioelectrical impedance analysis. Issue 1 (14th November 2020) - Fan, Xinru; Lin, Xiaoyu; Wu, Chunhua; Zhang, Nana; Cheng, Qiaofen; Qi, Hang; Konno, Kunihiko; Dong, Xiuping
Abstract: This study aimed to evaluate the freshness of ice stored rainbow trout by bioelectrical impedance measurements. Rigor mortis, ATP‐related components, K‐value, and hardness of rainbow trout muscle during storage were monitored along with impedance. The results showed that the progress of rigor mortis was accompanied by an increase in impedance. Impedance kept decreasing even in rigor state, and during the gradual resolution of rigor mortis with impedance change upon storage of fish was biphasic ( r = −0.944, p < .01). Thus, when impedance decreased close to the lowest value, K‐value was only about 61.57 ± 0.52%, but still exhibited a high pertinence ( r = −0.959, p < .01). A gradual decrease of the hardness of fish muscle upon storage of fish showed a close correlation ( r = 0.981, p < .01) with impedance decrease. These results suggested that the impedance measurement has a great potential for predicting the freshness of the rainbow trout during ice storage. Abstract : This study aimed to evaluate the freshness of ice stored rainbow trout by bioelectrical impedance measurements. These results suggested that impedance parameter could be applied to predict the rainbow trout freshness during ice storage.